Use of Banking in Online Transactions: A Case Study of Aceh Province - Nanda Rahmi, Aliasuddin, Weri, (Opción, 2019)
The objective of this study is to analyze the use of banking in online transactions in Aceh Province. Three regencies were purposively selected in this study, Banda Aceh, Aceh Barat, and Lhokseumawe. The regencies were selected because they can be reached via a direct flight from Medan, a major city in Indonesia. 400 respondents were randomly selected from these districts. There were 161 respondents from Banda Aceh, 113 from Lhokseumawe, and 126 from Aceh Barat. The results show that income and education were statistically and positively significant factors in determining banking usage, while other variables were not statistically significant